LEGAL PROTECTION OF THE AUTHORITY OF THE CURATOR IN THE MANAGEMENT AND SETTLEMENT OF BANKRUPT ASSETS - Ni Ketut Eka Patni; I Wayan Wiryawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This writing aims to determine the legal protection for the curator in exercising the authority to manage and settle bankrupt assets as well as the duties and authority of the curator in managing and controlling the bankrupt debtor's assets. This paper uses the normative juridical law research method by conducting a study and analysing laws and regulations related to the problem under study so that the results of the research above in the provisions of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Obligations for Payment of Debt do not guarantee legal protection for curators in carrying out their duties of managing and dealing with bankruptcy assets. Article 50 of the Criminal Code provides protection for curators who carry out their duties based on statutory regulations.